Study on zinc doped with aluminium oxide thin film towards structural and optical / Muhammad Fathi Fikri Burhan - Burhan, Muhammad Fathi Fikri (2018)
This project is about Zinc oxide, ZnO doped with Aluminium Oxide, AI2O3 were fabricated on substrates by depositing the thin layer. The thin film is prepared by using the spin-coating technique. The Aluminium oxide were varies by atomic mass of 2%, 4%, 6% and 8%. The aiming for this project is to prepare ZnO doped with AI2O3 thin film for structural and optical characterization. As for the characterization, the dopant solution between ZnO and AI2O3 for optical and structural properties. As for the result, these two characterization were observed for the analysis. The project is to check the changes in chacterization due to the result from these doping process. As for the result shows the changes for every doped atomic percentage between ZnO and AI2O3.